Risk of Acute Kidney Injury in Combat-Injured Patients Associated With Concomitant Vancomycin and Extended-Spectrum β-Lactam Antibiotic Use. (July 2021) - Yabes, Joseph M.; Stewart, Laveta; Shaikh, Faraz; Robben, Paul M.; Petfield, Joseph L.; Ganesan, Anuradha; Campbell, Wesley R.; Tribble, David R.; Blyth, Dana M.
Background: Multidrug-resistant infections complicating combat-related trauma necessitate the use of broad-spectrum antimicrobials. Recent literature posits an association between vancomycin (VANC) and piperacillin–tazobactam (VPT) combination therapy and acute kidney injury (AKI). We examined whether therapy with VPT was associated with an increased risk of AKI compared to VANC and other broad-spectrum β-lactam antibiotics (VBL) following combat-related injuries. Methods: Patients within the Trauma Infectious Disease Outcomes Study (TIDOS) who received ≥48 hours concomitant VPT or VBL started within 24 hours of each other were assessed. Exclusion criteria were receipt of renal replacement therapy and baseline creatinine >1.5 mg/dL. Acute kidney injury was defined by meeting any of the Risk, Injury, Failure, Loss, End Stage Renal Disease (RIFLE), AKIN, or VANC consensus guidelines criteria 3 to 7 days after therapy initiation. Variables significantly associated with AKI were used in inverse probability treatment weighting to perform univariate and subsequent logistic regression multivariate modeling to determine significant risk factors for AKI. Results: Sixty-one patients who received VPT and 207 who received VBL were included. Both groups had a median age of 24 years and initial median creatinine of 0.7 mg/dL. The VBL patients were more likely to have sustained blast injuries ( P = .001) and received nephrotoxic agents (amphotericin [ P = .002] and aminoglycosides [ P < .001]). In the VBL group, AKI incidence was 9.7% compared to 13.1% in the VPT group ( P = .438). Multivariate analysis identified a relative risk of 1.727 (95% CI: 1.027-2.765) for AKI associated with VPT exposure. Acute kidney injury severity generally met RIFLE Risk criteria and was 1 day in duration. Only 1 patient had persistent renal dysfunction 30 days after therapy completion. Conclusion: In this young and previously healthy, severely ill combat-injured population, VPT was associated with nearly twice the risk of AKI compared to VBL. Nevertheless, AKI was of low severity, short duration, and had high rates of renal recovery.